The abortion in Peru - Tang Bruigget, Luis (2015)
In all countries and in all times, abortion has been and remains a health problem with broad social impact; but in less developed countries where the socioeconomic conditions are critical, abortion causes dramatic situations with a very high social cost compromising the health and lives of women who experience it, either accidentally or on purpose.